2009
DOI: 10.1007/s11947-009-0284-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biochemical Hydrolysis of Persian Sturgeon (Acipenser persicus) Visceral Protein

Abstract: Chemical (pH 3.3, 70°C, 85°C; pH 12, 70°C, 85°C) and biochemical (Alcalase, Protamex, Neutrase, Flavourzyme, and Trypsin) hydrolysis of Persian sturgeon (Acipenser persicus) visceral protein was investigated. The results of this study revealed that there are significant differences between enzymes in terms of degree of hydrolysis (DH%; P < 0.05). Alcalase-hydrolyzed fish protein had the highest DH% (50.13%), and Trypsinhydrolyzed fish protein had the minimum DH% (14.21%). The highest DH% in chemical hydrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 17 publications
4
50
1
10
Order By: Relevance
“…In contrast, the investigators [32, 39, 40] had reported a decrease in the DH with prolonged incubation periods. Guerard et al [39] proposed the reduced DH observed with a prolonged incubation period might be caused by limited enzyme activity by the formation of reaction products at a high DH, the decreased concentration of peptide bonds available for hydrolysis, enzyme inhibition, and enzyme deactivation.…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, the investigators [32, 39, 40] had reported a decrease in the DH with prolonged incubation periods. Guerard et al [39] proposed the reduced DH observed with a prolonged incubation period might be caused by limited enzyme activity by the formation of reaction products at a high DH, the decreased concentration of peptide bonds available for hydrolysis, enzyme inhibition, and enzyme deactivation.…”
Section: Resultsmentioning
confidence: 92%
“…Generally, Alcalase® 2.4-L-assisted reactions have been repeatedly favored for fish hydrolysis, due to the high degree of hydrolysis that can be achieved in a relatively short time under moderate pH conditions, compared with the neutral or acidic enzymes (Kristinsson and Rasco 2000a, b;Hoyle and Merritt 1994;Shahidi et al 1995;Benjakul and Morrissey 1997;Aspmo et al 2005;Ovissipour et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…A number of peptides with significant biological activities have been identified in the enzymatic hydrolysis various marine tissue proteins, for example, antihypertensive activity peptides (Byun and Kim 2001;Qian et al 2007;Lee et al 2010;Tsai et al 2008;Zhao et al 2009;Lee and Song 2009;Sheih et al 2009), antioxidant peptides (Ovissipour et al 2009;Jung et al 2005b;Kim et al 2007a;Je et al 2008;Slizyte et al 2009;Cho et al 2008;Qian et al 2008), anticoagulant peptides (Jo et al 2008;Jung and Kim 2009;Jung et al 2002), antimicrobial peptides (Liu et al 2008;Battison et al 2008;Li et al 2008), angiotensin I converting enzyme (ACE)-inhibitory peptides (Kong et al 2009;He et al 2006;Cheung and Li-Chan 2010;), and mineral carrier peptides (Jung et al 2006;Jung and Kim 2007).…”
Section: Introductionmentioning
confidence: 99%